Pengaruh ROA, ROE dan NPM terhadap Harga Saham Sektor Keuangan pada Indeks LQ45 Periode 2018-2022 - Artawan, I Putu Agus; Kawiana, I Gede Putu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The caìpitaìl maìrket is aìn aìlternaìtive source of long-term funding aìmong vaìrious other aìlternaìtives for aì compaìny. One of the caìpitaìl maìrket instruments most populaìr with investors is shaìres. The shaìres thaìt aìre most in demaìnd by investors will experience aìn increaìse in stock prices aìnd returns, aìnd vice versaì. Shaìre prices aìre aì reflection of investors' expectaìtions regaìrding eaìrnings, caìsh flow aìnd return faìctors. To find out whether aì compaìny is good or not, it must be meaìsured by finaìnciaìl indicaìtors such aìs return on aìssets (ROAì) aìnd return on equity (ROE) aìnd Net Profit Maìrgin (NPM). The reseaìrch object is the Finaìnciaìl Sector compaìnies on the LQ45 Index which aìre listed on the Indonesiaìn Stock Exchaìnge (IDX) with aì populaìtion of 45 compaìnies. . Determining the number of saìmples waìs caìrried out using the purposive saìmpling method, determining the number of saìmples aìt 8 compaìnies. This reseaìrch uses quaìntitaìtive methods, descriptive reseaìrch, deductive reseaìrch, daìtaì collection methods, aìnd literaìture review. This study triaìl uses the T test aìnd F test. The test results from this reseaìrch show thaìt aìt the saìme time ROAì, ROE) do not haìve aì significaìnt effect on the stock prices of finaìnciaìl sector issuers in the 2018-2022 LQ45 Index, while NPM haìs aì significaìnt positive effect on stock prices. Finaìnciaìl Sector Issuers in the 2018-2022 LQ45 Index